Recent and future high energy experiments on QED nonlinear effects - Ispirian, K.A. (Вопросы атомной науки и техники, 2001)
A short review of the experiments on photon elastic scattering and splitting on Coulomb field of nuclei as well as on multiphoton Compton scattering and Breit-Wheeler pair production in strong electromagnetic field is given. Possible new QED nonlinear experiments are discussed.